2012
DOI: 10.1080/01635581.2012.697597
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cytokines as Potential Response Indicators to Dietary Freeze-Dried Black Raspberries in Colorectal Cancer Patients

Abstract: Oral consumption of freeze-dried black raspberries attenuated neoplastic changes in colorectal tissue markers of apoptosis, cell proliferation, and angiogenesis in colorectal cancer (CRC) patients. To determine, whether plasma concentrations of interleukin (IL)-1β, IL-2, IL-6, IL-8, IL-10, IL12p70, granulocyte macrophage colony stimulating factor (GM-CSF), interferon-γ, and tumor necrosis factor-α (TNF-α) were associated with berry treatment and changes in colorectal tissue markers of apoptosis, cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 21 publications
0
31
0
3
Order By: Relevance
“…In theory these interactions could alter the response to immune based cancer therapies, or the ability of the body’s endogenous immune system to recognize and eliminate developing tumors. To date, a limited number of other studies suggest BRB may have anti-inflammatory effects in a clinical setting [15,36,37]. For example, Mentor-Marcel et al ., conducted a clinical trial in colorectal cancer patients using oral administration of freeze-dried black raspberry powder in a slurry of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory these interactions could alter the response to immune based cancer therapies, or the ability of the body’s endogenous immune system to recognize and eliminate developing tumors. To date, a limited number of other studies suggest BRB may have anti-inflammatory effects in a clinical setting [15,36,37]. For example, Mentor-Marcel et al ., conducted a clinical trial in colorectal cancer patients using oral administration of freeze-dried black raspberry powder in a slurry of water.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mentor-Marcel et al ., conducted a clinical trial in colorectal cancer patients using oral administration of freeze-dried black raspberry powder in a slurry of water. Following three weeks of treatment, serum levels of increased GM-CSF and decreased IL-8 were observed [36]. In a second study, BRB was orally administered at 5% in the diet, based on average body weight to patients with Barrett’s esophagus, a premalignant condition that confers increased risk for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum insulin-like growth factor-1 levels were lower than pre-intervention in all patients, although not significantly [51]. Similarly, animal dietary studies with black raspberries reveal the chemopreventive capacities of the fruit in models of ulcerative colitis, several rodent models of colon cancer and adenoma, as well as humans [52,53,54,55,56,57,58]. …”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%
“…In 24 cancer patients receiving the same black raspberry treatment, plasma concentration of granulocyte macrophage colony stimulating factor (GM-CSF) was increased compared to measurements before initiating the berry treatment, while the other 8 plasma cytokines measured (IL-1β, IL-2, IL-6, IL-8, IL-10, IL-12p70, Interferon-γ, TNF-α) were not affected significantly. However, plasma concentrations of IL-8 decreased when the berry drink was consumed for longer than 10 days, suggesting that longer interventions may be needed for greater changes to occur [57]. In the same cohort of cancer patients non-targeted metabolomics in urine and plasma samples, showed significant changes in a number of metabolites (34 and 6, respectively) related to energy pathways, including increased carbohydrate and amino acid metabolites [57].…”
Section: The Role Of Dietary Berries In Various Types Of Cancermentioning
confidence: 99%
“…Results from the study showed that a 7% decrease in proliferation was observed in tumor tissues taken from patients when compared to their pre-intervention values. Another clinical trial investigating the impact of freeze-dried blackberry powder (60g/day, for 1 to 9 weeks) in colorectal cancer patients showed beneficial changes in GM-CSF and IL-8, markers for proliferation and apoptosis respectively [78].…”
Section: Data From Clinical Trialsmentioning
confidence: 99%